Effects of the Perindopril/Amlodipine Fixed-Dose Combination Therapy on the Left Ventricular Myocardial Deformation Properties and Arterial Stiffness Parameters in Patients with Arterial Hypertension - S. I. Bekmetova; G. Zh. Abdullaeva; G. A. Khamidullaeva; Sh. S. Fayzullaeva; Kh. F. Yusupova; F. A. Zakirova (International Journal of Biomedicine)
Background: Arterial hypertension (AH) is one of the main factors determining the high risk of cardiovascular complications and mortality. Early diagnosis of AH is a key point in its effective control and prevention of severe consequences. In recent years, the deformation properties of the left ventricle have been actively studied in the context of early diagnosis of AH and evaluation of the effectiveness of antihypertensive therapy. Our study aimed to assess effectiveness of the six-month perindopril/amlodipine fixed-dose combination (FDC) therapy on the deformation properties of the left ventricular (LV) myocardium and the elastic properties of arteries in AH patients. Methods and Results: This study included 55 patients (20 men and 35 women) with AH Grades 1-2 (ESC/ESH, 2018). The mean age of patients was 52.2±10.94 years; the average duration of AH was 7.51±6.77 years. All patients underwent general clinical examination, biochemical blood tests, standard transthoracic two-dimensional echocardiography with ECG synchronization, 2D-speckle tracking echocardiography (STE) with the assessment of global longitudinal strain [GLS] and strain rate (SR). Arterial stiffness was determined using applanation tonometry. All patients received a perindopril/amlodipine FDC. The drug dose, considering the maximum doses, was titrated at 2-week intervals to achieve a target blood pressure. The mean doses of perindopril and amlodipine were 4.4±1.2 mg/day and 7.86±2.5 mg/day, respectively. The final treatment results were determined after 6 months of antihypertensive therapy. Depending on the types of LV echo-geometry, AH patients were divided into three groups: Group 1 included 25 AH patients with normal LV geometry, Group 2 included 25 AH patients with LV concentric remodeling, and Group 3 included 5 AH patients with concentric LVH. The LV GLS values were -18.0±2.95%, -14.16±2.99%, and -12.4±1.87% in Groups 1, 2, and 3, respectively (P=0.0000). Intergroup analysis showed normal GLS value in Group 1, compared with Groups 2 and 3 (P1-2=0.0001 and P1-3=0.0007, respectively). Correlation analysis between the studied parameters revealed direct correlations of the LV mass index (LVMI) with GLS (rs=0.70, P=0.000), SR (rs=0.70, P=0.000), and pulse wave velocity (PWV) (rs=0.4, P=0.000). In addition, direct correlations were observed between the PWV and GLS (rs=0.50, P=0.000) and SR (rs=0.50, P=0.000). A direct correlation was also noted between LV ejection fraction (LVEF) and SR (rs=0.70, P=0.000). Before the start of therapy, the average systolic blood pressure (SBP) and diastolic blood pressure (DBP) were 163.05±13.7 mmHg and 96.4±10.7 mmHg, respectively. Analysis of the six-month perindopril/amlodipine FDC therapy in AH patients showed high antihypertensive efficacy. The target levels of SBP and DBP were achieved in 98.2% and 96.4% of patients, respectively. There was a significant positive dynamic in reducing LVMI (from 96.40±25.79 g/m2 to 82.3±24.5 g/m2, P=0.000). The LVEF also improved from 63.08±2.59% to 64.57±1.82% (P=0.000). The six-month perindopril/amlodipine FDC therapy positively influenced the LV myocardium deformation properties: GLS increased significantly from -15.0±3.2% to 19.09±2.8%, reaching the normative values (P<0.001); SR also increased significantly from 0.84±0.23s⁻¹ to -1.13±0.23s⁻¹ (P<0.001). The indicated therapy was effective for central hemodynamics and arterial stiffness. Conclusion: In AH patients with LV concentric hypertrophy, significant disturbances in the LV deformation properties are formed. The six-month perindopril/amlodipine FDC therapy provides good antihypertensive, cardioprotective, and vasoprotective efficacy, which is expressed in reliable regression of left ventricular hypertrophy, positive effect on the LV deformation properties, and increased elasticity of the arteries.